Utilization of Macromedia Flash Application Technology as Learning Media Development in Solving Islamic Religion Test Questions SPSS Data Processing - Wahyu Azhar Ritonga; Ahmad Habin Sagala; Syahrul Budiman; Fauzi Ahmad Syawaluddin; Syafaruddin (CV. AFDIFAL MAJU BERKAH, 2022)
The use of Multimedia Technology in the development of learning innovations in the digital era shows that the use of macromedia flash applications is very influential on the interest and motivation of students in solving both practice questions and exam questions, this is because in addition to using computer tools, the scores we get are directly listed. after doing the questions. Based on the results of testing using the SPSS application related to learning media and motivation on student satisfaction with a large sample of 30 people, the results obtained F = 21,645 with sig 0.000 meaning that there is a significant influence with the use of multimedia on student satisfaction in the implementation of learning.